A study on benefit distribution of agricultural product quality governance under the perspective of digital supply chain - Zhan Shuai; Wan Zhilan (Agricultural Economics (AGRICECON))
As the strategy for building a robust agricultural nation gains momentum and agricultural science and technology advances, the quality of agricultural products has seen significant improvement, accompanied by an increase in the economic income of agricultural producers and operators. Therefore, the fair and reasonable implementation of the revenue distribution of the agricultural supply chain is of great significance in improving the quality of agricultural products and ensuring the stable operation of the supply chain. The article focuses on the three main bodies of the agricultural supply chain, namely production and price co-integration enterprises, logistics service enterprises and sales enterprises, and utilises the matrix semi-tensor product to establish the Shapley value revenue allocation model of the interval cooperation game, so as to make the revenue allocation of the governance of agricultural products' quality in the digital supply chain more reasonable and scientific. Finally, numerical examples verify the Shapley value model, demonstrating that this revenue allocation scheme, when applied, can boost the overall supply chain's revenue through cooperative agricultural product quality management, elevate agricultural product quality and market competitiveness, and foster collaboration to ensure the stability of supply chain operations.